2014
DOI: 10.1017/s0263034613000992
|View full text |Cite
|
Sign up to set email alerts
|

Laser-driven ablation through fast electrons in PALS-experiment at the laser radiation intensity of 1–50 PW/cm2

Abstract: The paper is directed to the study of high-temperature plasma and ablation plasma formation as well as efficiency of the laser energy transfer to solid targets irradiated by laser pulses with intensities of 1–50 PW/cm2 and duration of 200–300 ps, i.e., at conditions corresponding to the characteristics of the laser spike designed to generate the igniting shock wave in the shock ignition concept. The experiments have been performed at Prague Asterix Laser System. The iodine laser delivered 250 ps (full width at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…With kT = 1.5 keV, ρd = 1.3×10 −2 g/cm 2 , S = 5.03 ×10 −5 cm 2 (corresponding to a spot radius of 40 μm), we find E h 70 J. This value is well below the energy absorbed in the interaction between the laser beam and the target, which is estimated [37] at a fraction of 30% of E L in our irradiation conditions, i.e., 200 J. We present this as a mere argument of plausibility for our simple model, well aware of the large uncertainties affecting the experimental α yield, expected proton yield, stopping power models, and estimate of the bulk temperature.…”
Section: A Modeling α-Particle Productionmentioning
confidence: 68%
See 2 more Smart Citations
“…With kT = 1.5 keV, ρd = 1.3×10 −2 g/cm 2 , S = 5.03 ×10 −5 cm 2 (corresponding to a spot radius of 40 μm), we find E h 70 J. This value is well below the energy absorbed in the interaction between the laser beam and the target, which is estimated [37] at a fraction of 30% of E L in our irradiation conditions, i.e., 200 J. We present this as a mere argument of plausibility for our simple model, well aware of the large uncertainties affecting the experimental α yield, expected proton yield, stopping power models, and estimate of the bulk temperature.…”
Section: A Modeling α-Particle Productionmentioning
confidence: 68%
“…Thermonuclear yield: Initially, we have tried to explain the α yield in terms of thermonuclear reactions occurring in the plasma plume and the warm, shocked target bulk [37]. In the following, we denote by η = ρ/ρ 0 the compression ratio between the density under shock, ρ, and the initial (ordinary) bulk density, ρ 0 .…”
Section: A Modeling α-Particle Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second case, this is due to the high intensity of a laser pulse, about 10 16 W/cm 2 , which is necessary for generation of an igniting shock wave. The effect of increasing ablation pressure due to energy transfer by fast electrons to dense plasma regions was experimentally observed in experiments [21,22] and in other ones [23,24,25] devoted to study of shock ignition.…”
Section: Energy Transmission From Fast Electronsmentioning
confidence: 98%
“…In our previous papers (Kalinowska et al, 2012;Gus'kov et al, 2014;Pisarczyk et al, 2014), it has been shown that the interferometric measurements in combination with the crater volume analysis can provide essential information about mechanisms of the laser radiation absorption. The ratio N/V cr (where N is the total electron number in the plasma plume and V cr is the crater volume in cm 3 ) defines a number of thermal electrons participating in the creation of crater volume unit (1 cm 3 ).…”
Section: Crater Volume Measurementsmentioning
confidence: 99%